Bear on bear. (Economist, 2016)
The article reports on evidence that two different Russia-based groups of computer hackers hacked into the computers of the Democratic Party in the U.S. in summer 2016 and cites concerns that Russia may carry out a cyber-attack on the 2016 U.S. election.